Modeling of elastoplastic crack propagation using finite element method with adaptive mesh / Syifaul Huzni and Ahmad Kamal Ariffin (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
Modeling of crack propagation using adaptive finite element mesh is presented in this paper. An adaptive mesh is applied to analyze two-dimension elastoplastic fracture during crack propagation. Displacement control approach and updated Lagrangean strategy are used to solve the non-linearity In geometry, material and boundary for plane stress crack problem. In the finite element analysis, the remeshing process is based on stress error norm coupled with h-version mesh refinement to find an optimal mesh. The crack is modeled by splitting crack tip node and automatic remeshing calculated for each step of crack growth. Crack has been modeled to propagate through the inter-element in the mesh. The crack is free to propagates without predetermine path direction. Maximum principal normal stress criterion is used as the direction criteria. Several examples are presented to illustrate the results achieved with current implementation.